PROSES KREATIF PENCIPTAAN ART FURNITURE KARYA BARATA SENA - Effendi, Salma Yusria; Supriyadi , Slamet; Hartono , Lili (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2024)
This research aims to (1) understand the creation of Barata Sena's art furniture through the lens of Victor Papanek's Function Theory, and (2) explore the artistic values of Barata Sena's art furniture. This study is a qualitative descriptive research. The data sources for this study include the informant (Barata Sena), events (the process of creating art furniture), and documents (articles on Barata Sena’s art furniture and photographs of the furniture pieces). Data collection was conducted through interviews, observations, and document analysis. The results of this research reveal that Barata Sena is a creative figure, and his creative process aligns with Victor Papanek's Function Theory. The ideas and concepts behind his art furniture, such as the floating table concept and the scarf bench, are inspired by elements from the artist’s surroundings. Both pieces are produced for the upper-middle-class market, particularly art gallery owners both domestically and internationally. Both works incorporate three elements of visual art: color, space, and texture, as well as the principles of visual art, including unity, balance, simplicity, and center of interest. Additionally, both works carry specific meanings relevant to human life.